Lignin derived carbon coated metal doped lithium iron phosphate, preparation method and lithium ion battery

By using lignin-derived carbon-coated metal-doped lithium iron phosphate material, the shortcomings of existing lithium iron phosphate materials in lithium ion diffusion and electronic conductivity are solved, and the power density and rate performance of lithium ion batteries are improved.

CN119873783APending Publication Date: 2025-04-25ZHEJIANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510211273.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing lithium iron phosphate materials have shortcomings in lithium ion diffusion and electronic conductivity, resulting in insufficient power density, small charge and discharge rate, need to be improved, and poor rate performance and capacity under low temperature and high temperature conditions.

Method used

The metal-doped lithium iron phosphate material is used to coat the metal-doped lithium iron phosphate material, and the lignin sulfonate is mixed with the iron source, phosphorus source and lithium source by hydrothermal method to form a metal-doped lithium iron phosphate precursor, and calcined in a secondary carbon source supplement and reducing atmosphere to obtain a metal-doped lithium iron phosphate positive electrode material coated with lignin-derived carbon.

Benefits of technology

It improves the power density and rate performance of lithium-ion batteries, enhances the lithium-ion transmission rate and electron conductivity, and improves the capacity retention rate of the material under different temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873783A_ABST
    Figure CN119873783A_ABST
Patent Text Reader

Abstract

The invention provides lignin-derived carbon-coated metal-doped lithium iron phosphate, a preparation method and a lithium ion battery. The preparation method comprises the following steps: step 1, mixing a lithium source, a phosphorus source and a dispersing agent according to a certain proportion, stirring to obtain a mixed solution I, mixing an iron source and the dispersing agent, stirring to obtain a mixed solution II, adding the mixed solution II into the mixed solution I while stirring to obtain a mixed solution III, adding lignosulfonate into the obtained mixed solution III, stirring and dispersing, and drying to obtain a lithium ion battery positive electrode material; performing hydrothermal treatment to obtain a solid precursor; and 2, centrifugally drying the solid precursor, mixing with a secondary carbon source, crushing together, and sintering to obtain the lithium iron phosphate. The lithium iron phosphate material with high-rate discharge performance is prepared by taking a biomass carbon source rich in papermaking waste liquid as a raw material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a lignin-derived carbon-coated metal-doped lithium iron phosphate, a preparation method and a lithium ion battery. Background Art

[0002] At present, the new energy vehicle market is booming, and lithium iron phosphate cathode materials are widely used due to their common raw material sources, relatively low cost, stable structure, non-toxicity, good safety and other advantages. However, from the structure of lithium iron phosphate, it can be seen that lithium ion diffusion is mainly a one-dimensional channel, which greatly limits the lithium ion deintercalation ability; and because the PO in the LFP structure 4 Tetrahedron hinders FeO 4 The connection of tetrahedrons leads to its poor electronic conductivity; these problems lead to several urgent problems in lithium iron phosphate, including: insufficient power density leads to low charge and discharge rate, energy density needs to be further improved, and lithium iron phosphate has poor rate performance and capacity under low temperature and high temperature conditions. In this regard, the commonly used carbon coating, nano-materialization, and element doping still cannot meet the performance requirements in a simple and effective way. The current application of carbon coating is mainly concentrated on carbon sources such as glucose and sucrose that form amorphous carbon after carbonization, but amorphous carbon is restricted by the coating layer and will hinder the transmission of lithium ions, while other non-continuous carbon coating layers with special structures, such as graphene, have the problem of high prices, which is not conducive to industrialization. Therefore, there is an urgent need for a carbon source that can have both conductivity and ion transmission and is widely available and cheap. On the other hand, lignin sulfonate, as the main component of paper mill wastewater, can achieve carbon coating and metal doping at the same time by virtue of its controllable structure of carbon derived after carbonization and its own metal salts, which not only recovers the huge potential pollution and waste of paper mills, but also meets the needs of lithium iron phosphate preparation. Therefore, we proposed a simple and efficient way to coat metal-doped lithium iron phosphate materials with lignin-derived carbon and a preparation method thereof, and provided a lithium-ion battery prepared from the positive electrode material. Summary of the invention

[0003] The purpose of the present invention is to provide a lignin-derived carbon-coated metal-doped lithium iron phosphate, a preparation method and a lithium ion battery in view of the deficiencies in the prior art.

[0004] The technical solution of the present invention is as follows:

[0005] The present invention provides a lignin-derived carbon-coated metal-doped lithium iron phosphate and a preparation method thereof:

[0006] Step 1: Mix a lithium source, a phosphorus source and a dispersant in a certain proportion and stir to obtain a mixed solution I; mix an iron source and a dispersant and stir to obtain a mixed solution II; add the mixed solution II to the mixed solution I while stirring to obtain a mixed solution III; add lignin sulfonate to the obtained mixed solution III, stir and disperse, and then hydrothermally obtain a solid precursor.

[0007] Step 2: After centrifugation and drying, the solid precursor is mixed with a secondary carbon source and pulverized together, and then sintered to obtain the lithium iron phosphate.

[0008] Preferably, the lignin sulfonate contains both a carbon source and a metal doped with a metal, thereby achieving dual purposes. The lignin sulfonate includes one or more of sodium lignin sulfonate, magnesium lignin sulfonate, and calcium lignin sulfonate. The metal doping is generally considered to be lithium doping.

[0009] Preferably, the added lignin sulfonate accounts for 2-4 wt% of the mass of the lithium iron phosphate.

[0010] Since lignin sulfonate should meet the requirements of carbon coating and metal doping, the amount of addition should be constrained by these two aspects. If it is too much, the metal doping will be too much, resulting in too many crystal defects, which is not conducive to the formation of lithium ion channels. If it is too little, the carbon coating layer will be uneven or too thin, making it difficult to achieve the effect of limiting particle growth and enhancing conductivity. In addition, sodium lignin sulfonate contains hydrophilic and hydrophobic groups, acting as a surfactant, effectively reducing liquid surface tension, which is conducive to controlling the crystal size of particles.

[0011] Preferably, the dispersant includes one or more of ethanol, water, N,N-dimethylformamide, acetone, isopropanol, and n-butanol.

[0012] Preferably, the molar ratio of the lithium source, iron source and phosphorus source, Li:Fe:P is (1.05-3):1:(0.5-3).

[0013] Preferably, the lithium source is a combination of one or more of lithium oxide, lithium hydroxide, lithium chloride, lithium acetate, lithium carbonate, lithium nitrate, lithium nitrite, lithium phosphate, lithium dihydrogen phosphate, lithium oxalate, lithium molybdate, and lithium vanadate;

[0014] Preferably, the iron source is a combination of one or more of ferrous chloride, ferrous nitrate, ferrous oxalate, ferric chloride, ferric hydroxide, ferric nitrate and ferric citrate;

[0015] Preferably, the phosphorus source is a combination of one or more of phosphoric acid, diammonium hydrogen phosphate, iron phosphate, and lithium dihydrogen phosphate.

[0016] Preferably, the content of the dispersant in step (1) is 50-300 wt % of the mass of the lithium iron phosphate.

[0017] Preferably, the hydrothermal temperature in step (1) is between 150° C. and 220° C., and the hydrothermal time is between 5 h and 12 h. The hydrothermal method can effectively use the metal components in the lignin sulfonate for Li-site doping, and the carbon coating obtained in this way is more uniform.

[0018] Preferably, the solid precursor is centrifugally dried after hydrothermal treatment. The drying temperature is preferably 60-90° C., and the drying time is preferably 4-8 hours.

[0019] The secondary carbon source in step (2) is preferably one or more of sucrose, glucose, ascorbic acid, citric acid, lignin, lignin sulfonate, etc.

[0020] The mass of the carbon element in the secondary carbon source accounts for 4-8wt% of the total mass of the lithium iron phosphate.

[0021] The pulverizing method in step (2) is preferably sand milling, ball milling, etc.

[0022] The sintering temperature in step (2) is preferably 750°C-800°C, and the calcination time is preferably 5-12h.

[0023] The sintering in step (2) should be carried out in an inert atmosphere or a reducing atmosphere, wherein the atmosphere includes one or more of hydrogen, argon, helium, and nitrogen. Preferably, cooling and grinding are performed after the secondary sintering.

[0024] Preferably, if Figure 1 As shown, the solid precursor in step 1 is in the form of a diamond-shaped column with a thickness of 300-800 nm and good uniformity and dispersion.

[0025] On the other hand, the present invention provides a positive electrode sheet comprising lithium iron phosphate obtained by the above preparation method.

[0026] In another aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet obtained by the above preparation method.

[0027] The beneficial effects of the present invention are as follows:

[0028] The method of the present invention utilizes the lignin sulfonate rich in papermaking wastewater to act as a carbon coating agent and a metal salt doping agent at the same time. First, a hydrothermal method is used to obtain a metal-doped lithium iron phosphate precursor by mixing an iron source, a phosphorus source, and a lithium source with lignin sulfonate. At this time, the lignin-derived carbon precursor has been coated to effectively control the particle size and morphology. After drying and crushing, a certain carbon source is added, and then further calcined in a reducing gas or inert gas atmosphere to obtain a lignin-derived carbon-coated metal-doped lithium iron phosphate positive electrode material. This method effectively utilizes biomass carbon that may cause environmental pollution, and the obtained carbon has a porous structure, which is conducive to electrolyte infiltration and Li +In addition, by metal doping, the Li position in the generated crystal is replaced, broadening the Li + The transmission channel further improves the ion transmission rate. By adding a small amount of carbon for the second time, an amorphous carbon layer is formed, which further improves the electron conduction rate and significantly improves the power density and rate performance. Lignin sulfonate has the function of a dispersant, and can obtain lithium iron phosphate positive electrode materials with good dispersion by making the particles negatively charged, effectively slowing down agglomeration. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a lithium iron phosphate particle coated with sodium lignin sulfonate and co-doped with sucrose. It is a diamond-shaped particle with a thickness of about 300nm. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0031] Comparative Example 1:

[0032] Weigh 0.1mol FeSO4 and 10mL ethylene glycol to prepare solution A, weigh 0.075mol lithium nitrate, 0.1mol phosphoric acid, and 12mL ethylene glycol to prepare solution B. After complete dissolution, add solution B dropwise into solution A under stirring. After mixing, heat at 160℃ for 6h, filter and dry to obtain a solid precursor. Take 1g of the precursor and mix with 0.05g citric acid, grind, and calcine at 700℃ in N2 atmosphere for 6h to obtain a secondary carbon-coated LFP material.

[0033] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0034] Comparative Example 2:

[0035] Weigh 0.1mol FeSO4 and 10mL ethylene glycol to prepare solution A, weigh 0.075mol lithium nitrate, 0.1mol phosphoric acid, and 12mL ethylene glycol to prepare solution B. After complete dissolution, add solution B dropwise into solution A under stirring. After mixing, add 0.008mol sodium lignin sulfonate, hydrothermal at 160℃ for 6h, filter and dry to obtain a solid precursor. Take 1g of the precursor, mix and grind, and calcine at 700℃ in N2 atmosphere for 6h to obtain lignin-coated and sodium-doped LFP material.

[0036] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0037] Comparative Example 3:

[0038] Weigh 0.1molFeSO4 and 8mL propanol to prepare solution A, weigh 0.075mol lithium oxalate, 0.1mol diammonium phosphate, and 10mL propanol to prepare solution B. After complete dissolution, add solution B dropwise to solution A under stirring. After the addition is complete, add 0.008mol lignin, hydrothermal at 160℃ for 6h, filter and dry to obtain a solid precursor. The precursor is mixed and ground with graphite, wherein the mass ratio of the precursor to graphite is 1:0.06, and calcined at 700℃ in N2 atmosphere for 6h to obtain a secondary coated LFP material.

[0039] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0040] Comparative Example 4:

[0041] Weigh 0.1molFeSO4 and 8mL propanol to prepare solution A, weigh 0.075mol lithium oxalate, 0.1mol diammonium phosphate, and 10mL propanol to prepare solution B. After complete dissolution, add solution B dropwise to solution A under stirring. After the addition is complete, add 0.008mol lignin and 0.008mol sodium nitrate, hydrotherm at 180℃ for 6h, filter and dry to obtain a solid precursor. The precursor is mixed and ground with graphite, wherein the mass ratio of the precursor to graphite is 1:0.06, and calcined at 700℃ in N2 atmosphere for 6h to obtain a secondary coated LFP material.

[0042] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0043] Comparative Example 5:

[0044] Weigh 0.1 mol FeSO4 and 8 mL propanol to prepare solution A, weigh 0.075 mol lithium oxalate, 0.1 mol diammonium phosphate, and 10 mL propanol to prepare solution B. After complete dissolution, add solution B dropwise to solution A under stirring. After the addition is complete, add 0.008 mol lignin and 0.008 mol sodium nitrate, hydroheat at 180°C for 6 hours, filter and dry to obtain a solid precursor. Take the precursor and calcine it at 700°C in N2 atmosphere for 6 hours to obtain a once-coated LFP material.

[0045] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0046] Comparative Example 6:

[0047] Weigh 0.1mol FeSO4 and 10mL ethylene glycol to prepare solution A, weigh 0.075mol lithium nitrate, 0.1mol phosphoric acid, and 12mL ethylene glycol to prepare solution B. After complete dissolution, add solution B dropwise into solution A under stirring. After the addition is complete, add 0.024mol sodium lignin sulfonate, hydroheat at 180℃ for 6h, filter and dry to obtain a solid precursor. Take 1g of the precursor and mix and grind with 0.05g citric acid, calcine at 700℃ in N2 atmosphere for 6h to obtain a secondary coated and sodium-doped LFP material.

[0048] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0049] Comparative Example 7:

[0050] Weigh 0.1mol FeSO4 and 10mL ethylene glycol to prepare solution A, weigh 0.075mol lithium nitrate, 0.1mol phosphoric acid, and 12mL ethylene glycol to prepare solution B. After complete dissolution, add solution B dropwise into solution A under stirring. After the addition is complete, add 0.008mol sodium lignin sulfonate, hydroheat at 180℃ for 6h, filter and dry to obtain a solid precursor. Take 1g of the precursor and calcine it at 700℃ in N2 atmosphere for 6h to obtain a coated and sodium-doped LFP material.

[0051] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0052] Embodiment 1:

[0053] Weigh 0.1mol FeSO4 and 10mL ethylene glycol to prepare solution A, weigh 0.075mol lithium nitrate, 0.1mol phosphoric acid, and 12mL ethylene glycol to prepare solution B. After complete dissolution, add solution B dropwise into solution A under stirring. After the addition is complete, add 0.008mol sodium lignin sulfonate, hydroheat at 180℃ for 6h, filter and dry to obtain a solid precursor. Take 1g of the precursor and mix and grind with 0.05g citric acid, calcine at 700℃ in N2 atmosphere for 6h to obtain a secondary coated and sodium-doped LFP material.

[0054] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0055] Embodiment 2:

[0056] Weigh 0.1mol FeSO4 and 10mL ethylene glycol to prepare solution A, weigh 0.075mol lithium nitrate, 0.1mol phosphoric acid, and 12mL ethylene glycol to prepare solution B. After complete dissolution, add solution B dropwise into solution A under stirring. After the addition is complete, add 0.008mol calcium lignin sulfonate, hydrothermal at 180℃ for 6h, filter and dry to obtain a solid precursor. Take 1g of the precursor and mix and grind with 0.05g citric acid, calcine at 700℃ in N2 atmosphere for 6h to obtain a secondary coated and calcium-doped LFP material.

[0057] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0058] Embodiment 3:

[0059] Weigh 0.1molFeSO4 and 8mL propanol to prepare solution A, weigh 0.075mol lithium oxalate, 0.1mol diammonium phosphate, and 10mL propanol to prepare solution B. After complete dissolution, add solution B dropwise to solution A under stirring. After the addition is complete, add 0.008mol sodium lignin sulfonate, hydrothermal at 180℃ for 6h, filter and dry to obtain a solid precursor. The precursor is mixed and ground with graphite, wherein the mass ratio of the precursor to graphite is 1:0.06, and calcined at 700℃ in N2 atmosphere for 6h to obtain a secondary coated LFP material.

[0060] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0061] Embodiment 4:

[0062] Weigh 0.1molFeSO4, 8mL propanol to prepare solution A, weigh 0.075mol lithium oxalate, 0.1mol diammonium phosphate, 10mL propanol to prepare solution B, after complete dissolution, add B solution dropwise to A solution under stirring, after adding, add 0.004mol sodium lignin sulfonate, 0.004mol calcium lignin sulfonate, hydrothermal at 180℃ for 6h, filter and dry to obtain a solid precursor. Take the precursor and mix it with graphite, wherein the mass ratio of precursor to graphite is 1:0.06, calcine at 700℃ N2 atmosphere for 6h, and obtain a secondary coated LFP material.

[0063] The prepared positive electrode material was used to make a button battery with PVDF as a binder and SP as a conductive agent, and the charge and discharge test was carried out at 2-3.8V.

[0064] Sample name Voltage range First cycle capacity (mAh / g) Capacity retention rate (%) Comparative Example 1 2-3.8V 118.2(1C) 78.2 (200 laps) Comparative Example 2 2-3.8V 131.7(1C) 86.2 (200 laps) Example 1 2-3.8V 128.5(1C) 96.3 (100 laps) Comparative Example 3 2-3.8V 121.3(1C) 89.1(100 laps) Comparative Example 4 2-3.8V 116.2(1C) 82.1(100 laps) Comparative Example 5 2-3.8V 97.1(1C) 72.3 (100 laps) Comparative Example 6 2-3.8V 85.2(1C) 67.2 (100 laps) Comparative Example 7 2-3.8V 120.3(1C) 83.2(100 laps) Example 2 2-3.8V 122.1(1C) 93.6(100 laps) Comparative Example 3 2-4.0V 128.6(1C) 72.3 (100 laps) Example 2 2-4.0V 135.2(1C) 95.6(100 laps) Comparative Example 3 2-3.8V 121.3(1C) 89.2 (100 laps) Example 4 2-3.8V 119.3(1C) 92.3 (100 laps) Example 5 2-3.8V 123.2(1C) 91.2(100 laps)

[0065] Conclusion: It can be seen from Comparative Example 1 and Example 1 that after coating with sodium lignin sulfonate, the cycle stability and capacity are improved, which is mainly due to the sodium doping to increase the lithium ion channel space and the lithium ion diffusion rate, and after one coating, the stability and conductivity are increased. It can be seen from Comparative Example 2 and Example 1 that without secondary coating, the carbon source is insufficient, resulting in limited coating effect and decreased cycle stability. It can be seen from Comparative Example 3 and Example 2 that after calcium doping with calcium lignin sulfonate, the working voltage is increased, and the structural stability under high pressure is improved. It can be seen from Comparative Example 3 and Example 4 that the role of lignin sulfonate can be replaced by carbon source and metal salt. Although the performance is reduced compared with carbon source and metal source, the huge cost advantage can make up for the slight difference in performance. It can be seen from Comparative Example 5 and Example 1 that the material without secondary coating is lacking in cycle and rate performance. It can be seen from Comparative Example 6 and Example 3 that after excessive addition of lignin sulfonate, the material hinders ion transmission due to excessive substitution sites, resulting in a decrease in material cycle and capacity. From Comparative Example 7 and Example 3, it can be seen that, without the aid of reducing salts such as citric acid, the material can appropriately play a reducing role due to the presence of lignin sulfonate, but the relative performance is insufficient. From Example 3 and Example 4, it can be seen that different lignin sulfonates can be calcined in a certain ratio and still have a good effect.

Claims

1. A method for preparing lignin-derived carbon-coated metal-doped lithium iron phosphate, characterized in that: The steps include: Step 1, mixing a lithium source, a phosphorus source, and a dispersant in a certain proportion and stirring to obtain a mixed solution I, mixing an iron source and a dispersant and stirring to obtain a mixed solution II, adding the mixed solution II to the mixed solution I while stirring to obtain a mixed solution III, adding lignin sulfonate to the obtained mixed solution III, stirring and dispersing, and hydrothermally obtaining a solid precursor; Step 2: After centrifugation and drying, the solid precursor is mixed with a secondary carbon source and pulverized together, and then sintered to obtain the lithium iron phosphate.

2. The preparation method according to claim 1, characterized in that: The lignin sulfonate contains both a carbon source and a metal doped with a metal, and the lignin sulfonate includes one or more of sodium lignin sulfonate, magnesium lignin sulfonate, and calcium lignin sulfonate.

3. The preparation method according to claim 1, characterized in that: The added lignin sulfonate accounts for 2-4 wt% of the mass of lithium iron phosphate.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the lithium source, the iron source and the phosphorus source is (1.05-3):1:(0.5-3).

5. The preparation method according to claim 1, characterized in that: The content of the dispersant in step 1 is 50-300wt% of the mass of the lithium iron phosphate; the hydrothermal temperature in step 1 is between 150°C and 220°C, and the hydrothermal time is between 5h and 12h. The hydrothermal method can effectively use the metal components in the lignin sulfonate for Li-position doping, and the carbon coating obtained in this way is more uniform.

6. The preparation method according to claim 1, characterized in that: After hydrothermal treatment, the solid precursor is centrifugally dried, the drying temperature is preferably 60-90° C., and the drying time is preferably 4-8 hours.

7. The preparation method according to claim 1, characterized in that: The mass of carbon element in the secondary carbon source accounts for 4-8wt% of the total mass of lithium iron phosphate; the secondary carbon source is preferably one or more of sucrose, glucose, ascorbic acid, citric acid, lignin, lignin sulfonate, etc.

8. The preparation method according to claim 1, characterized in that: The solid precursor in step 1 is in the form of a rhombus-shaped column with a thickness of 400-800 nm.

9. A positive electrode sheet, characterized in that The invention relates to lithium iron phosphate obtained by any preparation method according to claims 1 to 8.

10. A lithium ion battery, characterized in that A positive electrode sheet comprising the positive electrode sheet prepared according to claim 9.

Citation Information

Patent Citations

  • Method for preparing high-conductivity lithium iron phosphate anode material

    CN102013468A

  • Method of preparing lithium iron phosphate cathode material through hydrothermal method, and the cathode material

    CN105591100A

  • Preparation method of positive electrode material, positive electrode material and battery

    CN106207178A

  • Preparation method of manganese-doped lithium iron phosphate electrode material

    CN108390057A

  • Preparation method of aluminum-doped high-compaction long-circulation lithium iron phosphate positive electrode material

    CN113979420A